2013
DOI: 10.1242/jeb.083154
|View full text |Cite
|
Sign up to set email alerts
|

Loss of integration is associated with reduced resistance to oxidative stress

Abstract: SUMMARYOne cellular mechanism thought to be particularly important as a constraint on lifespan and life-history strategies is oxidative stress. Susceptibility to oxidative stress is influenced by a number of antioxidant defences, whose effectiveness depends on the synergistic and competitive interactions among them (biochemical integration). It is generally assumed that exposure to oxidative stress is detrimental, but it is also possible that low level oxidative stress has a positive effect on integration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 62 publications
(77 reference statements)
5
54
0
1
Order By: Relevance
“…Indeed, in zebra finches, when flight activity in a test cage was increased by moving perches over a period of 2 h, immediate ROM concentration increased but there was no change in antioxidant capacity, as measured by the concentration of antioxidant enzymes (Costantini et al, 2013). In the present study, flight activity was increased by plucking three primary feathers from each wing.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Indeed, in zebra finches, when flight activity in a test cage was increased by moving perches over a period of 2 h, immediate ROM concentration increased but there was no change in antioxidant capacity, as measured by the concentration of antioxidant enzymes (Costantini et al, 2013). In the present study, flight activity was increased by plucking three primary feathers from each wing.…”
Section: Discussionmentioning
confidence: 42%
“…A previous study conducted on birds showed that flight activity increases ROM concentration (Costantini et al, 2013). Indeed, in zebra finches, when flight activity in a test cage was increased by moving perches over a period of 2 h, immediate ROM concentration increased but there was no change in antioxidant capacity, as measured by the concentration of antioxidant enzymes (Costantini et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study by Costantini and collaborators (2014) (see also Costantini et al 2013), adult zebra finches exposed to short episodes of heat stress in adulthood showed increased long-term survival and resilience only if they had been previously exposed to thermal stress before reaching sexual maturity. Since in our study, the birds continued to experience the food shortage throughout the period when survival was monitored, it seems likely that the protracted exposure to unpredictable food may have triggered hormetic responses, behavioural and/or physiological that increased likelihood of survival and, at least to some extent, prolonged lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, plasma non-enzymatic antioxidants were higher in great tits (Parus major) with clipped feathers (which increases flight effort) than in individuals with unclipped feathers (Vaugoyeau et al, 2015). Interestingly, zebra finches (Taeniopygia guttata) flown at rapid speeds had increased levels of plasma uric acid but not antioxidant enzymes compared with those of control birds (Costantini et al, 2013). Many studies have shown that uric acid levels increase during flapping flight and migration.…”
Section: Endogenous Enzymesmentioning
confidence: 97%